(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2021)
In recent decades, and on the basis of what is called the “archival turn”, different theoretical and methodological reflections have been made about the archives, their origins, configurations and uses. On the one hand, other types of archives have begun to receive attention. Thus, outside imperial, state or official repositories, the analysis of family or personal records, as well as that of peasant and indigenous communities, have been brought into focus in studies which intensify the oppositions between the public and the private spheres, orality and writing, paper documents and other types of material media. Taking these contributions as the starting point, and within the framework of our own research studies about indigenous peoples, we set forth from the dilemma we face when reflecting upon the dialogues and tensions generated around the construction of the past, when those who engage in dialogue and dispute are actors with dissimilar experiences, interests and power (indigenous people, academicians, state agents). On the basis of the idea put forth by Fabian about a theory – and praxis of – coevalness, understood as a condition for the existence of a dialogic encounter between people and societies, and accepting this author’s invitation to “share our pasts”, the aim of this article is to provide some methodological notes on the place of the “archive” as a possible point of intersection and dialogues. Therefore, our main objective is to rethink/question the “archive”, considering it, as Stoler does, not only as a site of knowledge retrieval, but essentially as a place of knowledge production.